Temperate snake community in South America: Is diet determined by phylogeny or ecology? - Bellini, Gisela Paola (2015)
Communities are complex and dynamic systems that change with time. The first attempts to explain how they were structured involve contemporary phenomena like ecological interactions between species (e.g., competition and predation) and led to the competition-predation hypothesis. Recently, the deep history hypothesis has emerged, which suggests that profound differences in the evolutionary history of organisms resulted in a number of ecological features that remain largely on species that are part of existing communities. Nevertheless, both phylogenetic structure and ecological interactions can act together to determine the structure of a community. Because diet is one of the main niche axes, in this study we evaluated, for the first time, the impact of ecological and phylogenetic factors on the diet of Neotropical snakes from the subtropical-temperate region of South America. Additionally, we studied their relationship with morphological and environmental aspects to understand the natural history and ecology of this community. A canonical phylogenetical ordination analysis showed that phylogeny explained most of the variation in diet, whereas ecological characters explained very little of this variation. Furthermore, some snakes that shared the habitat showed some degree of diet convergence, in accordance with the competition-predation hypothesis, although phylogeny remained the major determinant in structuring this community. The clade with the greatest variability was the subfamily Dipsadinae, whose members had a very different type of diet, based on soft-bodied invertebrates. Our results are consistent with the deep history hypothesis, and we suggest that the community under study has a deep phylogenetic effect that explains most of the variation in the diet.